Why do cracks occur in the weld joint of Ti-22Al-25Nb alloy during post-weld heat treatment? - Shao, Ling; Zhang, Xinyu; Chen, Yingwei; Zhu, Liu; Wu, Sujun; Liu, Qijie; Li, Weiwei; Xue, Na; Tu, Zhibiao; Wang, Tianle; Zhang, Jitang; Dai, Sheng; et al. (Frontiers in Materials, 2023)
Ultrasonic pulse frequency tungsten inert gas welding technology was adopted to join Ti-22Al-25Nb alloy. There were some cracks in the Ti-22Al-25Nb alloy weld joint after post-weld heat treatment. The hardness and Young’s modulus of α2, O, and β/B2 phases in Ti-22Al-25Nb alloy were examined with an in situ nanoindentation technique. The phase transition stresses of three different phases in the weld joint of Ti-22Al-25Nb alloy were analyzed to explain why cracks occur in the weld joint of Ti-22Al-25Nb alloy during post-weld heat treatment. The results show that mean hardness is highest for the α2 phase, second-highest for the O phase, and lowest for the β/B2 phase; the mean Young’s modulus has the same trend in Ti-22Al-25Nb alloy. Phase transition stress results in cracks in the weld joint of Ti-22Al-25Nb alloy during post-weld heat treatment. By improving post-weld heat treatment, the ultimate strength of the Ti-22Al-25Nb alloy weld joints reaches 750 MPa, which is 72.5% that of the base material.